2014
DOI: 10.3390/md12063190
|View full text |Cite
|
Sign up to set email alerts
|

New Prenylxanthones from the Deep-Sea Derived Fungus Emericella sp. SCSIO 05240

Abstract: Four new prenylxanthones, emerixanthones A–D (1–4), together with six known analogues (5–10), were isolated from the culture of the deep-sea sediment derived fungus Emericella sp. SCSIO 05240, which was identified on the basis of morphology and ITS sequence analysis. The newstructures were determined by NMR (1H, 13C NMR, HSQC, HMBC, and 1H-1H COSY), MS, CD, and optical rotation analysis. The absolute configuration of prenylxanthone skeleton was also confirmed by the X-ray crystallographic analysis. Compounds 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
14
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(18 citation statements)
references
References 18 publications
(29 reference statements)
4
14
0
Order By: Relevance
“…The occurrence of prenylxanthone derivatives from Emericella sp. XL029 is in agreement with the previous ndings, [8][9][10][11][12][13][14] indicating that the isolation of these compounds might be a useful chemotaxonomic marker of the Emericella genus. The results of preliminary anti-agricultural pathogenic fungal and antibacterial assays suggested that these isolated prenylxanthone derivatives showed moderate activity.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The occurrence of prenylxanthone derivatives from Emericella sp. XL029 is in agreement with the previous ndings, [8][9][10][11][12][13][14] indicating that the isolation of these compounds might be a useful chemotaxonomic marker of the Emericella genus. The results of preliminary anti-agricultural pathogenic fungal and antibacterial assays suggested that these isolated prenylxanthone derivatives showed moderate activity.…”
Section: Discussionsupporting
confidence: 90%
“…SCSIO 05240, and E. striata. [6][7][8][9][10][11][12][13][14] Furthermore, fungi of the Emericella species are the sexual states of Aspergillus species, the perfect states of Aspergillus, has been the source of various classes of bioactive compounds. 8,23,24 During our studies in searching for novel bioactive compounds from plant endophytic fungi, we have isolated the interesting pigment-producing fungal strain (XL029) associated with the leaves of Panax notoginseng, belonging to the genus Emericella.…”
Section: Introductionmentioning
confidence: 99%
“…was described by Park et al [ 7 ]. After that, many biologically active secondary metabolites have been isolated from deep-sea fungi and evaluated for their activities against cancer, pathogenic fungi, bacteria, virus, and larval settlement [ 1 , 7 , 8 , 9 ]. Many bioactive metabolites have shown potential as an excellent resource for the discovery of new drugs [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…In the course of our study on marine derived microbes, several active metabolites were isolated [ 13 , 14 , 15 , 16 ]. In our previous study, two aromatic butyrolactones were reported from the same fungus, A. flavipes [ 17 ].…”
Section: Introductionmentioning
confidence: 99%